Multicriteria-based estimation of selection of commercial property construction site/Komercinių objektų statybos vietos parinkimo vertinimas įvairiais aspektais - Ustinovičius, Leonas; Stasiulionis, Andrius (Journal of Civil Engineering and Management, 2001)
When investing into real estate, especially into commercial buildings, it is very important to choose a right location. Location should be chosen in order to meet highest and best usage of the future commercial building. Usefulness and efficiency of location are determined by qualities which may be divided into the following groups: 1) common qualities; 2) special qualities characteristic to a particular activity. Great attention should be paid to city land use model. Development of Vilnius City has been based on several models and due to a great variety and instability of location criteria, selection of land site for commercial property becomes complicated. Real estate investments require creation of cardinal criteria system, which could facilitate the selection of location. Exhaustive information about location is of vital importance for investments into real estate. Therefore research of information systems related to geographical location, GIS, must be conducted. Using cardinal criteria system we would be able to match multicriteria decision-making methods suitable for solving discrete alternative problems. After having determined cardinal criteria, most suitable multicriteria decisionmaking methods are as follows: 1) linear reckoning/ascription method; 2) simple add weighting method (SAW); 3) hierarchical add weighting method; 4) ELECTRE method; 5) method of distance from ideal point (TOPSIS). From the practical point of view it is difficult to define ideal location as possibility to compensate by other criteria or attach to one the particular criterion, as every location is unique in its one way. ELECTRE method based on binary comparison of options in order to determine whether the criteria of option meet criteria's predomination or contradict it was chosen as one of the most suitable innovative selective methods for choosing the commercial property's location.Article in Lithuanian.First Published Online: 30 Jul 2012